Improving Care for Chronic Conditions Current Practices and Future Trends in Health Plan Programs - Mattke, Soeren (RAND Corporation, 2015)
The need for better management of chronic conditions is urgent. Many health plans have developed innovative approaches to improving care for their members with chronic conditions. This report documents the current range of health plans' chronic care management services, identifies best practices and industry trends, and examines factors in plans' operating environment that limit their ability to optimize chronic care programs.